2016
DOI: 10.2337/dc15-1899
|View full text |Cite
|
Sign up to set email alerts
|

Effective Translation of an Intensive Lifestyle Intervention for Hispanic Women With Prediabetes in a Community Health Center Setting

Abstract: OBJECTIVEThe Diabetes Prevention Program (DPP) demonstrated that weight loss from intensive lifestyle intervention (ILI) in adults with prediabetes could decrease progression to type 2 diabetes. Inner-city, low-income Hispanic women are at high risk for developing type 2 diabetes; however, this type of intervention is not well established in this group. We hypothesized that a DPP intervention modified for a community health center (CHC) setting would decrease weight and improve metabolic measures in Hispanic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 13 publications
0
59
0
1
Order By: Relevance
“…We have not systematically searched for more recent primary studies not included in the reviews considered here. However, the latest update from the DPP is in keeping with the results reviewed,43 as are the results of additional recent trials,44 45 including trials based in routine practice, where clinical benefits were found to be modest 4647 We excluded non-English language publications that we were unable to access (see figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…We have not systematically searched for more recent primary studies not included in the reviews considered here. However, the latest update from the DPP is in keeping with the results reviewed,43 as are the results of additional recent trials,44 45 including trials based in routine practice, where clinical benefits were found to be modest 4647 We excluded non-English language publications that we were unable to access (see figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies varied widely in sample size (N=20–312). Four studies recruited female participants only, 1619 and four others were composed of largely (≥70%) female samples. 2023 Participant mean age ranged from 27.8 to 52 years, participants were largely of Mexican descent, and the majority were overweight or obese (BMI >25).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…2023 Participant mean age ranged from 27.8 to 52 years, participants were largely of Mexican descent, and the majority were overweight or obese (BMI >25). Six studies used participant BMI >24 or 25 as an inclusion criterion, 16,17,2225 and three studies used elevated HbA1c 20,22 or prediabetes diagnosis via oral glucose tolerance test 19 as inclusion criteria.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations